Oropharyngeal Dysphagia in Infants and Children with Infantile Pompe Disease - Jones, Harrison N.; Muller, Carolyn W.; Lin, Min; Banugaria, Suhrad G.; Case, Laura E.; Li, Jennifer S.; O’Grady, Gwendolyn; Heller, James H.; Kishnani, Priya S. (Dysphagia, 2010)
Pompe disease is a rare genetic progressive neuromuscular disorder. The most severe form, infantile Pompe disease, has historically resulted in early mortality, most commonly due to cardiorespiratory failure. Treatment with enzyme replacement therapy (ERT) using alglucosidase alfa (Myozyme ® ) has extended the lifespan of individuals with this disease. With the introduction of ERT and the resultant improved survival, dysphagia is being encountered clinically with increasing regularity though systematic data remain unavailable. We retrospectively studied the oropharyngeal swallowing of 13 infants and children with Pompe disease using videofluoroscopy before initiation of ERT, allowing for baseline swallow function to be established in an untreated cohort. Dysphagia was present in all 13 subjects, even in a participant only 15 days old. Oral stage signs were present in 77%, most frequently a weak suck in 69%. Pharyngeal stage signs were present in 100%, including a pharyngeal swallow delay in 92% and pharyngeal residue in 77%. Airway invasion was present in 76.9% of subjects, including penetration in five (38.46%) and silent aspiration in an additional five (38.46%). No relationship in the relative involvement of swallowing, gross motor function, and cardiac disease appeared to be present.